Synthesis of Perfluoroalkyl-Substituted Oxindoles through Organophotoredox-Catalyzed Perfluoroalkylation of N-arylacrylamides with Perfluoroalkyl Iodides - Yang, Zhiyong; Tang, Anjiang (Synlett, 2019)
An efficient process was developed for the perfluoroalkylation of N-arylacrylamides through an organocatalyzed photoredox/cyclization reaction of N-arylacrylamides with inexpensive perfluoroalkyl iodide reagents. The reaction employs an inexpensive organic dye, eosin Y, as the photoredox catalyst and is run under irradiation by a 26 W LED lightbulb.
Keywords: oxindoles; cyclization; perfluoroalkylation; photoredox reaction